PENGARUH KONSENTRASI JAMUR DIPO TERHADAP HASIL FERMENTASI SEDIAAN KOMBUCHA DENGAN SUBSTRAT TEH HITAM - A. Tenriugi Daeng Pine; Latifah Rahman; M. Natsir Djide; Syahruddin Kadir (Universitas Islam Negeri Alauddin Makassar, 2013)
The aims of this study to get the valid data about the suitable starter concentration so thaht we can get the good kombucha preparation. This research was done by organoleptic test (taste, odour, colour) pH value by using the Schott pH-meter, the sugar concentration reduced by reduction-oxidation titration method by using Luff Schoorl solution, and the total value of acetic acid becteria by using GYCA (Glucose Yeast Calcium carbonat Agar) medium to the black tea extract which was fermentatedwith the mushroom of kombucha tea starter used 5%w/v, 10%w/v, 15%w/v, 5%v/v, 10%v/v, dan 15%v/v during 7 days. The result of analysis showed that in 15%w/v concentration has pH value = 2,96; total value of aid bacteria = 5,4.104 colony/ml; organoleptic value = 24; total concentration of acid = 0,14%; the sugar concentration reduced = 2,75% was the very suitable to get the good kombucha preparation with black tea substrat